(untitled) (Research, Society and Development, 2022)
The study aims to present the importance of breastfeeding even in the negative circumstances of the pandemic by COVID-19 and to clarify the care and measures to be taken by mothers infected by the virus. The study was based on an integrative literature review with a qualitative approach, the following descriptors were used for the search strategy: Breastfeeding, Coronavirus and Postpartum Period, both crossed by the boolean operator AND. The databases used to construct this article were: Literatura Latino Americana e do Caribe em Ciências da Saúde (LILACS) and Medical Literature Analysis and Recovery System Online (MEDLINE). Clinical and randomized studies, present in Portuguese, Spanish and English and that followed the period from 2019 to 2022, were included to compose the search filters. Duplicate studies, integrative review, books, letters to the editor and previous notes were excluded. The findings show that there is a lack of scientific production on the subject, on the other hand, it was possible to notice that at the beginning of the pandemic there was a lot of fear of mothers feeding their babies, for fear of contracting COVID-19 infection, however, over the years, it was observed that there is no transmissibility through breastfeeding. Finally, it was possible to identify in the researches found that there is no evidence of infection through breast milk and that breastfeeding has immunological benefits for babies, which may be a protective factor in the scenario of the pandemic for the NB (newborn). Thus, it is extremely necessary that the professionals intensify the importance of breastfeeding continues, without interruption, guiding and clarifying the care to be taken. In addition, it is necessary to strengthen future research, as it is still a very reluctant topic in the pandemic scenario and there are specific guidelines for each case.